2008
DOI: 10.1111/j.1551-2916.2008.02487.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Far Infrared Emission Properties of Tourmaline Powders Modified with a Rare Earth

Abstract: and W is OH À , F À , or O 2À ) powders and cerium nitrate as raw materials. The results of Fourier transform infrared spectroscopy (FTIR) show that rare earth Ce can enhance the far infrared emission properties of tourmaline. Through characterization by transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), the mechanism by which rare earth Ce acts on the far infrared emission property of tourmaline was systematically studied. The XPS spectra show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…3), and leading to an apparent shrinkage of unit cell volume of tourmaline at low content of Ce. 17 The unit cell volume shrinkage will benefit the improvement of far infrared emission property of tourmaline. 17 23 …”
Section: Xrdmentioning
confidence: 99%
See 2 more Smart Citations
“…3), and leading to an apparent shrinkage of unit cell volume of tourmaline at low content of Ce. 17 The unit cell volume shrinkage will benefit the improvement of far infrared emission property of tourmaline. 17 23 …”
Section: Xrdmentioning
confidence: 99%
“…Therefore, the far infrared emission property of tourmaline needs further improvement to meet practical applications. In our previous research, 17 we found that Ce 4+ of CeO 2 oxidizes * Author to whom correspondence should be addressed. Fe 2+ to Fe 3+ inside the tourmaline, which leads to the unit cell volume shrinkage and consequently enhances the far infrared emission property of tourmaline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle is based on the GaussianLorentzian function: valence's peak area ratio is proportional to its content ratio. Compared with experimental data and calculated spectra reported in literatures [32,34], the peaks of Fe 3+ (Fe2p 3/2 713.4 eV and Fe2p 1/2 726.4 eV) and Fe 2+ (Fe2p 3/2 711.7 eV and Fe2p 1/2 724.4 eV) can be easily identified, and the test curves were divided into four parts using of these binding energies. Then the peak area of corresponding valence can be obtained by XPSpeak software fitting.…”
Section: Xps Survey Spectra With High Resolution Of Fe2pmentioning
confidence: 99%
“…This result has a certain correlation with the far infrared emissivity of samples. The most likely explanation for this is that the transformation from Fe 2+ to Fe 3+ oxidized by Ce 4+ because of the radius of Fe 2+ (0.078 nm) is larger than that of Fe 3+ (0.0645 nm) [32,33]. …”
Section: Phase Compositions and Lattice Parametermentioning
confidence: 99%